Small Players Ruling the Hard Game: siRNA in Bone Regeneration. (8th March 2016) - Ghadakzadeh, Saber; Mekhail, Mina; Aoude, Ahmed; Hamdy, Reggie; Tabrizian, Maryam
ABSTRACT: Silencing gene expression through a sequence‐specific manner can be achieved by small interfering RNAs (siRNAs). The discovery of this process has opened the doors to the development of siRNA therapeutics. Although several preclinical and clinical studies have shown great promise in the treatment of neurological disorders, cancers, dominant disorders, and viral infections with siRNA, siRNA therapy is still gaining ground in musculoskeletal tissue repair and bone regeneration. Here we present a comprehensive review of the literature to summarize different siRNA delivery strategies utilized to enhance bone regeneration. With advancement in understanding the targetable biological pathways involved in bone regeneration and also the rapid progress in siRNA technologies, application of siRNA for bone regeneration has great therapeutic potential. High rates of musculoskeletal injuries and diseases, and their inevitable consequences, impose a huge financial burden on individuals and healthcare systems worldwide. © 2016 American Society for Bone and Mineral Research.